Relay-race deformation mechanism during uniaxial tension of cylindrical samples of carbon steel: using digital image correlation technique - T.V. Tretiakova; V.E. Vildeman (Fracture and Structural Integrity)
The work deals with experimental study of macro localization of plastic yielding occurrences of structural carbon steel, research of singularity of deformation wave processes by complex use of contemporary test equipment and high effective digital image correlation method. Evolution of nonuniform axial strain fields on surface of cylindrical samples during uniaxial tension was registered, time dependences were drawn, and a ‘relay-race’ mechanism of material deformation was found out at the stage of yield plateau forming. Strain concentration ratio was estimated for several material deformation stages.